Cardiac Troponin-I And CK-MB for Risk Stratification in Acute Myocardial Infarction (First Attack): A Comparative Study (Bangladesh Journal of Medical Biochemistry, 2013)
Myocardial infarction is associated with release of two important enzymes. The enzymatic diagnosis is mainly based on the measurement of CK-MB and troponin-I. Cardiac troponin- I(cTnI) is known to have higher specificity and analytic sensitivity than CK-MB for detection of myocardial injury & risk stratification. These are used both as diagnostic and prognostic marker. This prospective observational study included 60 patients of 40-65 years age range, diagnosed as acute myocardial infarction. The mean ages were 50± 8 years and 53±8 years respectively. Male and female patients included were 86.7% and 13.3%; BMI was 25.3±1.5. The two important cardiac markers troponin-I and CK-MB were studied in 60 patients, admitted in the hospital with acute MI. Blood samples to estimate these markers were collected from the patients after admission at 6-9 hours, 9-24 hours and after 24 hours and their mean values with ±SD were calculated, evaluated and compared between the two groups of patients with low and high risk MI. The patients with low risk MI were those who recovered early and the high risk patients improved later in comparison to low risk group. Out of 60 patients, 37 had troponin-I level>1.5 ng /ml. Among them 29 developed high risk MI and 8 recovered earlier than high risk group. 23 patients had troponin-I